Die Suid-Afrikaanse Kapelaansdiens (SAKD) en staatsbeleid tydens die Grensoorlog, 1966-1989 - Bredenkamp, I.; Wessels, A. (Acta Theologica, 2011)
During the Border War (1966-1989), also known as the Bush War or the Namibian War of Independence, the accusation was made that chaplains serving in the South African Chaplaincy Service (SACHS) endorsed and propagated the policy of apartheid. This article gives an historical perspective on the question whether chaplains were able to function independently, in accordance with the doctrines of their respective denominations, or whether they became liveried servants to state politics during the Border War. Diverse cultures, underpinning different socio-political viewpoints, were involved, as is evident from the oral testimonies of chaplains serving during the time of the war. By reassessing historical identities and interpreting the nature of the controversial values and sentiments that prevailed during the specific timeframe, this article endeavours to create a better understanding of the past.